2011 IEEE International Conference on Robotics and Automation 2011
DOI: 10.1109/icra.2011.5980524
|View full text |Cite
|
Sign up to set email alerts
|

Incremental construction of the saturated-GVG for multi-hypothesis topological SLAM

Abstract: Abstract-The generalized Voronoi graph (GVG) is a topological representation of an environment that can be incrementally constructed with a mobile robot using sensor-based control. However, because of sensor range limitations, the GVG control law will fail when the robot moves into a large open area. This paper discusses an extended GVG approach to topological navigation and mapping: the saturated generalized Voronoi graph (S-GVG), for which the robot employs an additional wall-following behavior to navigate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Construction of Multi-layer Inputs 1) Data Representation on GVG: In this paper, our multilayer inputs is represented by the hierarchical generalized Voronoi graph (GVG) [4], a topological graph which has been successfully applied to navigation, localization and mapping. The general representation of GVG is composed of meet-points (locations of three-way or more equidistance to obstacles) and edges (feasible paths between meet-points which are two-way equidistance to obstacles) [28]. We adopt the same resolution as in our previous work [23] to construct the first layer GVG, and then higher layers of GVGs are constructed to describe the environment at different levels of granularity.…”
Section: Multi-layer Construction and Decision Makingmentioning
confidence: 99%
“…Construction of Multi-layer Inputs 1) Data Representation on GVG: In this paper, our multilayer inputs is represented by the hierarchical generalized Voronoi graph (GVG) [4], a topological graph which has been successfully applied to navigation, localization and mapping. The general representation of GVG is composed of meet-points (locations of three-way or more equidistance to obstacles) and edges (feasible paths between meet-points which are two-way equidistance to obstacles) [28]. We adopt the same resolution as in our previous work [23] to construct the first layer GVG, and then higher layers of GVGs are constructed to describe the environment at different levels of granularity.…”
Section: Multi-layer Construction and Decision Makingmentioning
confidence: 99%
“…117 In order to be able to recover from incorrect loop closures, Tully et al 112 introduced a multi-hypothesis approach based on a tree expansion algorithm specifically conceived for edge-ordered graphs, 32 as well as a series of pruning rules to keep the number of hypothesis under control. Recently, Tao et al 107 discussed the benefits of saturated generalized Voronoi graphs (S-GVG), that employ a wall-following behavior to navigate within sensor range limits, and performed SLAM using a similar hypothesis tree. Finally, Werner et al 119 suggested applying stochastic local search (SLS) to produce the topological map.…”
Section: Voronoi Graphs and Neighboring Information Choset And Nagatmentioning
confidence: 99%
“…FastSLAM [11][12][13][14] is an efficient approach to SLAM based on particle filtering. Some other efficient algorithms have also been proposed, such as Rao-Blackwellized particle filters (RBPF), 15,16 Graph-SLAM, 17,18 Topological SLAM, [19][20][21] EM-based Incremental SLAM 22 and Prediction-based SLAM (P-SLAM). 23 However, most of the existing approaches assume that pre-placed artificial landmarks or sufficient natural features are available in the environment.…”
Section: Introductionmentioning
confidence: 99%